Masalah Penugasan Pada Teknisi Untuk Perbaikan Mesin Produksi Dalam Skenario Ketidakpastian - Mohammad Syaiful Pradana; Siti Alfiatur Rohmaniah; Awawin Mustana Rohmah (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2025)
The problem of technician assignment in terms of production machine repair is the main focus of this research to help smooth the production process, maintain the availability and performance of the machine where the repair process depends on the efficiency of the technician team. Unexpected machine damage, the level of complexity of machine repair, as well as different competencies and availability of technicians are part of the uncertainty conditions in machine repair. This research focuses on the uncertainty scenario (Sk1, Sk2, Sk3) of technician assignment for production machine repair with a case study involving 3 machines (M1, M2, M3) and 4 technicians (T1, T2, T3, T4). The method used adapts the Hurwicz and Bayes rules (H+B) where this method is designed for one-time decisions and pure strategies with the aim of minimizing the total machine repair time. The results of the application of the optimal solution method found are assignments (T1 - M1) 6.67 hours, (T2 - M2) 8.46 hours, and (T4 - M3) 7.86 hours and resulting in a minimum total repair time of 22.99 hours. Further research could be conducted to extend the model to consider different repair costs and technician capabilities as well as other approaches to uncertainty such as Fuzzy Logic or Stochastic Programming.